TRADISI LAWA SAFAR DI NEGERI MORELLA, KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Muhammad Saiful Manilet; H. Rajab Rajab (Jurnal Studi Islam, 2022)
Abstract : This research is about the Lawa Safar tradition, a term used by the Morella people to refer to the bath routine on the last Wednesday of Safar month in the Islamic calendar every year. Its aim is to find out its historical roots, analyze it from the aspects of Islamic law, and see the prospects for its development. This descriptive qualitative research relies on literature sources which are strengthened by interviews of ritual actors. From the analysis carried out, it is not certain when Lawa Safar began to be carried out, but as in other places that carry out a similar tradition, the Lawa Safar ritual is influenced by the assumption that Safar is the month of disaster. Lawa Safar is carried out as an effort to repel reinforcements', a prayer to save people from danger and disaster. There is nothing contrary to the teachings of Islam in the series of Lawa Safar rituals, therefore, this tradition can be maintained as one of the syiars of Islam. Moreover, with the status of Morella today as one of the main tourist destinations in Maluku, it is very possible for the Lawa Safar tradition to be developed into one of the annual religious tourism events.Abstrak : Penelitian ini tentang tradisi Lawa Safar,  istilah yang digunakan oleh orang Morella untuk menyebut ritual mandi di Rabu terakhir bulan Safar dalam penanggalan Islam setiap tahun. Tujuan penelitian adalah untuk mengetahui akar sejarahnya, menganalisisnya dari aspek hukum Islam, dan melihat prospek pengembangannya. Tipe penelitian deskriptif kualitatif, data data diperoleh dari  literatur pustaka dan hasil wawancara dari pelaku ritual. Dari analisis yang dilakukan, tidak diketahui dengan pasti kapan Lawa Safar mulai dilaksanakan, tapi seperti halnya di tempat-tempat lain yang melakukan tradisi serupa, ritual Lawa Safar dipengaruhi anggapan bahwa Safar adalah bulan datangnya bencana. Lawa Safar dilakukan sebagai upaya tolak bala’, doa untuk menghindarkan masyarakat dari bahaya dan bencana. Tak ada hal yang bertentangan dengan ajaran Islam dalam rangkaian ritual Lawa Safar, karena itu, tradisi ini dapat dipertahankan sebagai salah satu syiar Islam. Status negeri Morella sekarang sebagai salah satu tujuan utama wisatawan di Maluku, maka tradisi Lawa Safar sangat mungkin dikembangkan menjadi salah satu event wisata religi tahunan.